The Impacts of the International Student Mobility Program on the Employability Skills: Indonesian Student Perceptions - Simbolon, Nurmala Elmin; Hadipranata, Qurrata Ayunina Ciptantri; Nastiti, Tur; Almahendra, Rangga; Amalia, Oki Almas; Wibowo, Nadia Utami; Anggoro, Kiki Juli; binti Zaaba, Zuraidah (Jurnal Pendidikan Progresif, 2025)
The Impacts of International Student Mobility Program on the Employability Skills: Indonesian Students’ Perceptions. The Indonesia International Student Mobility Awards (IISMA) is an Indonesian government scholarship program that enables Indonesian students to spend one semester studying in overseas English-medium instruction (EMI) classes. The article discusses students’ perceptions of the impact of the IISMA on employability skills:  interpersonal communication, critical thinking, and teamwork skills. This quantitative study employed a questionnaire to measure three skill variables, utilizing a pre- and post-test design involving 1941 students. The online questionnaire distribution was done from November 27 to December 13, 2023.  The data of this study were analyzed using Jamovi 2.3.24 software.Key findings demonstrate the significance of the Paired T-Test results (p-value < 0.001), and the difference in the increase in those skills experienced by the IISMA students had a significant effect size increase, specifically d = 0.5 for interpersonal communication skills, d = 0.667 for critical thinking, and d = 0.667 for teamwork skills. The Independent Samples T-Tests for students’ demographic information show that the value of employability skills among academic students outperforms that of vocational participants. ANCOVA analysis results show a significant correlation between students’ perceptions and their home institutions and host institutions. The research highlights the benefits of IISMA for the Indonesia Emas generation. Recommendations on critical considerations in designing programs and selecting host institutions are provided to ensure program sustainability. Keywords: english medium instruction (EMI), experiential learning, indonesia emas.